the postmodern turn in childhood studies and its pedagogical implications - luo, yao (childhood & philosophy, 2024)
This paper reflects on the postmodern shift in childhood studies and its impact on education. As scholars interrogate the modern notion of childhood, the discourse of postmodernism has entered the realm of childhood studies, yielding various new perspectives on childhood. The key characteristics of the postmodern shift in childhood studies include: 1) the rejection of essentialism regarding childhood and the recognition of the diversity inherent in it; 2) the deconstruction of binary oppositions and the advocacy for the heterogeneous nature of childhood and the concept of "becoming-child"; 3) the dissolution of the modern subject associated with childhood and the reconstruction of the postmodern subject. Postmodern childhood studies will bring some positive impacts to the field of education, such as focusing on the differences among children rather than abstracting them into a unified map, removing adultism from education, and emphasizing the construction of new forms of child subjectivity in education. However, at the same time, it will also bring many challenges to education, such as questioning the essence of childhood and good education, shaking the foundation of educational existence brought by the dissolution of childhood, and the loss of educational significance due to the fluid and changing construction of child subjectivity. This underscores the importance of acknowledging that as education embraces the discourse of postmodern childhood, both its promises and perils will permeate the educational domain.